A Comparative Study of NAK80 Steel and Beryllium Copper Moulds for Injection Moulding of Polypropylene Material - Aliff Abdul Rahman,; Aznizam Ahmad, (Progress in Engineering Application and Technology, 2024)
In manufacturing products using plastic, the most widely used process is injection moulding. Objective in this project is to investigate the effect of processing parameters on cycle time of injection-moulded parts produced from NAK80 steel and beryllium copper moulds. Then, to compare cycle time, part shrinkage and weight of moulded parts produced with NAK80 steel and beryllium copper moulds of Polypropylene homopolymer material in injection moulding. In injection moulding process, a mould cavity is injected with the polymer, and solidifies by follow the shape of the mould. Plastic injection processes included the plasticization, injection, packing or holding, cooling, ejection, and part quality control. Injection moulding machine parameters such as melt temperature and injection pressure are selected to analyses the cycle time. Coordinate measuring machine was used to measure the shrinkage level of the Polypropylene homopolymer sample cups. Next, the weight of Polypropylene homopolymer sample cup was measured by a weighing scale. Experiment of injection moulding process parameters will be fulfil using Polypropylene homopolymer by using pre-hardened NAK80 steel and beryllium copper insert material. These methods are accompanied for the parts by using plastic injection method which is constructing to be produce. Other than that, after part weight was measured it proceed with measure the shrinkage level of mould parts then emphasize the result from both moulds material parts that more effectively. The comparison of NAK80 and BeCu works well based on the results and data that has been taken during the testing process and its will get the suitable outcomes for the both moulds.